Neutral Substitutions Occur at a Faster Rate in Exons Than in Noncoding DNA in Primate Genomes - Subramanian, Sankar; Kumar, Sudhir (Genome Research, 2003)
Point mutation rates in exons (synonymous sites) and noncoding (introns and intergenic) regions are generally assumed to be the same. However, comparative sequence analyses of synonymous substitutions in exons (81 genes) and that of long intergenic fragments (141.3 kbp) of human and chimpanzee genomes reveal a 30%–60% higher mutation rate in exons than in noncoding DNA. We propose a differential CpG content hypothesis to explain this fundamental, and seemingly unintuitive, pattern. We find that the increased exonic rate is the result of the relative overabundance of synonymous sites involved in CpG dinucleotides, as the evolutionary divergence in non-CpG sites is similar in noncoding DNA and synonymous sites of exons. Expectations and predictions of our hypothesis are confirmed in comparisons involving more distantly related species, including human–orangutan, human–baboon, and human–macaque. Our results suggest an underlying mechanism for higher mutation rate in GC-rich genomic regions, predict nonlinear accumulation of mutations in pseudogenes over time, and provide a possible explanation for the observed higher diversity of single nucleotide polymorphisms (SNPs) in the synonymous sites of exons compared to the noncoding regions.